The Distributional Impact of Population Ageing - Omar A Aziz; Christopher Ball; John Creedy; Jesse Eedrah (New Zealand Government, The Treasury, 2013)
This paper examines the potential distributional impacts of demographic change, particularly population ageing, and changes to labour force participation that are projected to arise over the next 50 years. The approach involves calibration weighting of the Treasury's microsimulation model, Taxwell, based on the New Zealand Household Economic Survey. The weights are adjusted for each projection year to ensure that a range of population aggregates (by age and gender) match the projected values provided by Statistics New Zealand. Measures of income inequality and poverty, along with the incidence of income tax, Goods and Services Tax and a number of components of government spending (namely health and education) across age groups, are obtained. The results suggest that population ageing and expected changes in labour force participation, in isolation, do not have a significant impact on population-level measures of income inequality.
Keywords: H24; I14; I24; J1; H24; 330; Inequality; population ageing; survey calibration; poverty; fiscal incidence